CHARACTERIZATION OF ACID MINE DRAINAGE FORMATION WITH NET TOTAL ACID PRODUCING POTENTIAL (NTAPP) METHOD ON STONE SAMPLES OF PT. ABC - Naufal Faiz (NIM : 12114079), Ahmad
In the mining process, especially during excavation, the material inside the earth is exposed, including acid-forming materials. If that things happen can cause the appearance of acid mine drainage. Acid mine drainage can be managed by knowing the potential forming of acid mine drainage from the rock firstly. To find out the potential forming of acid mine drainage from a rock, geochemical characterization of rocks is needed. Rock geochemical characterization tests that are widely used today are static tests and kinetic tests. Commonly used static tests are static tests (pH paste, Acid Base Accounting (ABA), Net Acid Generating (NAG)). At this time the Net Total Acid Producing Potential (NTAPP) test has been introduced. In the NTAPP test can be sorted between acid-forming sulfur with sulfur which does not form acid. This research was conducted to characterize rock samples using the NTAPP test and ABA static test and then analyzed the differences in the characterization results of the two methods. The results of rock geochemical characterization using both methods will be verified with the results of kinetic tests. Kinetic test was carried out using the Free Draining Column Leach Test (FDCLT) method, followed by measurements of physical and chemical parameters in leach water. The maximum potential value of total acidity in the NTAPP method is generally lower than the Maximum Potential Acidity-MPA value in the ABA method. This is because the NTAPP test only calculate the amount of sulfur that has the potential to form acids (sulfides and sulfates). However, this difference still provides a classification of acid water formation potential from each sample that is verified by kinetic test with samples of ABC 01 and ABC 02 rocks classified as PAF (Potentially Acid Forming) rocks, while samples of ABC 03 rocks are classified as NAF rocks (Non-Acid Forming).